2011
DOI: 10.1111/j.1365-2923.2011.04154.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement in medical education: current state and future directions

Abstract: To prepare the next generation of doctors to make meaningful contributions to the quality mission, we propose the following call to action. Firstly, a major effort to build faculty capacity, especially among teachers of QI, should be instigated. Secondly, accreditation standards and assessment methods, both during training and at end-of-training certification examinations, should explicitly target these competencies. Finally, and perhaps most importantly, we must refocus our attention at all levels of training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
160
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(167 citation statements)
references
References 61 publications
1
160
0
6
Order By: Relevance
“…27 The first step in quality improvement relies on adequate accreditation and assessment methods available during training to ensure that specific competencies of trainees are met. 28 Aware of such shortcomings, the American Board of Urology and the ACGME have developed a Milestones project with the goal of standardizing assessment of Urology program graduates. 29 Opportunities for improvement do exist; a simulation based curriculum in general surgical laparoscopic training has been shown to decrease operative time, improve resident performance and decreased complications.…”
Section: Discussionmentioning
confidence: 99%
“…27 The first step in quality improvement relies on adequate accreditation and assessment methods available during training to ensure that specific competencies of trainees are met. 28 Aware of such shortcomings, the American Board of Urology and the ACGME have developed a Milestones project with the goal of standardizing assessment of Urology program graduates. 29 Opportunities for improvement do exist; a simulation based curriculum in general surgical laparoscopic training has been shown to decrease operative time, improve resident performance and decreased complications.…”
Section: Discussionmentioning
confidence: 99%
“…They include difficulty balancing educational demands with clinical workload, variability in faculty and trainee enthusiasm, and lack of faculty expertise. 3,4 This Rip Out describes a strategy for implementing a QI curriculum to meet Accreditation Council for Graduate Medical Education common requirements and expectations under an evolving Pathways to Excellence approach for CLER. 5 …”
Section: The Challengementioning
confidence: 99%
“…4 Based on its extensive experience, Cincinnati Children's Medical Center identified 4 key drivers for resident involvement in QI: (1) knowledge of key concepts of improvement science; (2) resident-initiated quality QI projects and facilitation of ''buy in''; (3) protected time for learning and development of QI projects; and (4) a sustainable system to keep track of resident-initiated projects. 2.…”
Section: What Is Known-ensuing Effective Qi Projectsmentioning
confidence: 99%
“…Faculty are applying these new skills in three ways: (1) to formal curricula that incorporate quality improvement concepts and methods, (2) in educational activities on specific improvement or safety tasks, or (3) by incorporating trainees as participants in local quality improvement initiatives. 7 A systematic review of 41 published QI curricula for students and residents demonstrated improvements in knowledge, processes and clinical outcomes. 8 Additionally, a number of organizations such as the World Health Organization (WHO), Institute for Healthcare Improvement (IHI), and the Mayo Clinic have developed resources for QI training.…”
Section: Quality Improvementmentioning
confidence: 99%